2016
DOI: 10.1080/09273948.2016.1245758
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Role of Intravitreal Corticosteroids as an Adjuvant to Antibiotics in Infectious Endophthalmitis

Abstract: Infectious endophthalmitis is an important cause of vision loss worldwide. This entity most often occurs as a complication of intraocular surgery especially following cataract surgery or intravitreal injection. Endophthalmitis is regarded as a serious complication following ocular surgery and the final visual outcome is fundamentally contingent on timely recognition and intervention. Intravitreal and oral antibiotics in combination with pars plana vitrectomy or vitreous aspiration remain the mainstay in the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…A major determinant for the prognosis of endophthalmitis is timely diagnosis that facilitates early intervention. 16 However, despite early recognition of the infection and treatment with IVAB, the disease may progress and contribute to the formation of RD.…”
Section: Discussionmentioning
confidence: 99%
“…A major determinant for the prognosis of endophthalmitis is timely diagnosis that facilitates early intervention. 16 However, despite early recognition of the infection and treatment with IVAB, the disease may progress and contribute to the formation of RD.…”
Section: Discussionmentioning
confidence: 99%
“…Few authors have reported the use of intravitreal corticosteroids. There is likely insufficient support in the current literature to recommend intravitreal corticosteroids as a standard of care [ 51 ].…”
Section: Medical Treatmentmentioning
confidence: 99%
“…pneumoniae endophthalmitis thought to have no underlying risk factors at admission, receiving prompt intravitreal antibiotics and vitrectomy, but who demonstrated the dismal visual outcome that remains associated with this condition. More research is being done to clarify the role of corticosteroids [19]. Patients such as this one, presenting with suspected choroidal abscesses, require a high index of suspicion, and urgent medical assessment to initiate both sepsis screening and immediate empirical treatment.…”
Section: Discussionmentioning
confidence: 99%